2018
DOI: 10.1259/bjr.20170498
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a radiomic signature to predict HPV (p16) status from standard CT imaging: a multicenter study

Abstract: This study provides proof of concept that molecular information can be derived from standard medical images and shows potential for radiomics as imaging biomarker of HPV status. Advances in knowledge: Radiomics has the potential to identify clinically relevant molecular phenotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
127
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(133 citation statements)
references
References 37 publications
4
127
1
1
Order By: Relevance
“…CT radiomics has previously been evaluated for prediction of overall survival and HPV status [22][23][24][25] . The performance of the distributed HPV models (AUC 0.73-0.80) is comparable with previously published results (AUC 0.70-0.80).…”
Section: Discussionmentioning
confidence: 99%
“…CT radiomics has previously been evaluated for prediction of overall survival and HPV status [22][23][24][25] . The performance of the distributed HPV models (AUC 0.73-0.80) is comparable with previously published results (AUC 0.70-0.80).…”
Section: Discussionmentioning
confidence: 99%
“…76,77 Overall, prevalence of HPV+ and HPVÀ cases (positive/negative = 0.62/0.38 for 116+ vs 71À) in our dataset was considered reasonable, and was higher than in other similar studies. [11][12][13][14] While investigators have found radiomic features to be relatively insensitive to specific image acquisition techniques among different scanners and institutions for patients, 57,78 others have shown this to be a potentially problematic issue requiring more detailed investigation. 22,79 Textural features require interpolation to isotropic voxel spacing to be rotationally invariant, and to allow comparison between image data from different samples, cohorts, or batches.…”
Section: Discussionmentioning
confidence: 99%
“…Z-score standardization was performed to normalize the MRI signal from different images. Lastly, the images were resampled to a common isotropic resolution of 2 mm (as in [ 39 ]) using B-spline interpolation. Intensity values of the MRI were discretized using 32-bins histogram discretization.…”
Section: Methodsmentioning
confidence: 99%